Recommendations for Creating Inclusive Classroom Andragogy: Perspectives of Graduate Students with Learning Disabilities - Boggs, Marcee (My University, 2021)
Guided by principles of Disability Critical Race Theory (2013) and Universal Instructional Design (2006), the purpose of this study is to examine the structural inequalities in higher education that marginalize students with disabilities, identify the unique needs of graduate students with learning disabilities, and identify the ideal classroom characteristics that would reduce or eliminate the need for self-disclosure and accommodations. This phenomenological qualitative research study focuses on the voices of fourteen graduate students with self-identified learning disabilities to highlight the unique needs of graduate students and the areas for improvement. Participants shared their reason for self-disclosing and seeking accommodations, or not. They shared the differences between their undergraduate and graduate experiences. Participants also conceptualized an ideal classroom, based on previous experience, and shared those characteristics. Themes included the need for: flexibility, diverse ways of presenting information and assessing knowledge, structured courses with clear instructions and reminders, and an open and honest dialogue pertaining to disability. These characteristics directly aligned with Universal Instructional Design principles. The study also includes information about the benefits of disability and the experience of going through education during a global pandemic. To conclude, students provide direct recommendations for praxis to faculty who have students with disabilities in their classrooms.
Doctor of Educational Leadership (EdD)
Keywords: learning disability; graduate students; andragogy; Universal Instructional Design; DisCrit; social model